2004
DOI: 10.1148/radiol.2331031375
|View full text |Cite
|
Sign up to set email alerts
|

Supplemental Oxygen Causes Increased Signal Intensity in Subarachnoid Cerebrospinal Fluid on Brain FLAIR MR Images Obtained in Children during General Anesthesia

Abstract: These findings are consistent with the hypothesis that increased arterial oxygen tension and consequently increased CSF Po(2) resulting from administration of high Fio(2) during general anesthesia are responsible for the increased CSF signal intensity noted on brain FLAIR MR images.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 5 publications
(2 reference statements)
3
26
0
3
Order By: Relevance
“…CSF hyperintensity on FLAIR has been related to blood, proteinaceous content, inflammatory exudates or pyogenic material, anesthesia, and/or high inspired fractional oxygen concentrations (Ͼ50%). 2 None of these conditions were contributory in the current patient. Single-shot, fast spin-echo FLAIR, which has been noted to result in spuriously high signal intensity in the CSF spaces, was not used in this case.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…CSF hyperintensity on FLAIR has been related to blood, proteinaceous content, inflammatory exudates or pyogenic material, anesthesia, and/or high inspired fractional oxygen concentrations (Ͼ50%). 2 None of these conditions were contributory in the current patient. Single-shot, fast spin-echo FLAIR, which has been noted to result in spuriously high signal intensity in the CSF spaces, was not used in this case.…”
Section: Discussionmentioning
confidence: 80%
“…Increasing contrast dosage and delay in imaging are additional factors that contribute to extracellular contrast accumulation. 2,3,7 Animal studies have shown that gadolinium agents cross the BBB in healthy dogs, a phenomenon that is more evident with higher contrast agent concentrations. 8 Most previously reported cases of CSF gadolinium enhancement in clinical patients are seen in conjunction with higher than usual contrast doses and in the setting of poor renal clearance.…”
Section: Discussionmentioning
confidence: 99%
“…Daha sonra yapılan bazı klinik çalışmalar da, HSA'nın oksijenle bağlantılı olduğu varsayımını destekler niteliktedir. [8][9][10][11][12] Örneğin bir çalışmada, azot protoksit kullanılan ve inspire edilen oksijen fraksiyonun düşük olduğu gruptaki hiçbir hastada HSA görülmemiştir. 8 Dolayısıyla artık yaygın kabul gören görüş, MR'daki FLAIR görüntülerde HSA'ya yolaçan nedenin oksijen olduğu şeklindedir.…”
Section: J Clin Exp Invest Wwwjceionlineorg Vol 3 No 4 December 2012unclassified
“…Daha önce gerçekleştirilen çalış-malar da, hem yüz maskesiyle hem de endotrakeal tüp ya da larengeal maske gibi havayolu gereçleriy-le verilen oksijenin HSA'ya neden olduğunu göster-mişlerdir. [8][9][10][11][12] Ancak bu konuda yapılan diğer yayınlar incelendiğinde, çalışma dizaynları arasında farklılıklar olduğu göze çarpmaktadır.…”
Section: J Clin Exp Invest Wwwjceionlineorg Vol 3 No 4 December 2012unclassified
See 1 more Smart Citation